An evaluation of the effects of response interruption redirection and matched stimulation on vocal stereotypy. (3rd December 2019) - Gibney, Cara; Phillips, Katrina J.; Arnold‐Saritepe, Angela; Taylor, Sarah Ann
Abstract : Stereotypy is one of the core diagnostic features of autism spectrum disorder and warrants behavioral intervention when it negatively impacts the person's life. The aim of this study was to evaluate the effectiveness of noncontingent matched stimulation (NCR‐M) compared with response interruption redirection (RIRD) on reducing levels of vocal stereotypy in the natural environment. Interventions were compared using an alternating treatments design followed by generalization and maintenance phases, which utilized lay people as instructors. Results showed that both RIRD and NCR‐M resulted in a reduction in vocal stereotypy for three out of four participants within an educational setting. An increase in appropriate vocalizations was found for two out of four participants for both interventions. These results suggest that both NCR‐M and RIRD were effective in reducing levels of vocal stereotypy, yet their effects on appropriate communication remain undetermined. Social validity scores were obtained following the study, which demonstrated that both interventions were met with approval across a variety of measures.